The peculiarities of the wind power generating autonomous system exploitation in the underground mountain iron-ore mining - Сінчук, Олег Миколайович; Бойко, Сергій Миколайович (Technology audit and production reserves, 2014)
The possibility and specifics of wind power complex functioning in operating underground iron-ore mining were analyzed. Aerodynamic features of ventilation airflows in underground iron-ore mining and their impact on the wind power plant operation were investigated. The design of wind power plant was substantiated and proposed for the practical implementation to realize its optimum possible efficiency. The structure of electromechanical part of the wind power complex and the control system for it with a predicted reliability and quality capacity of power supply to consumers of underground iron-ore mining electric power were developed. The behavior was investigated, and the control law was developed for the regulator of capacitive excitation current of induction generator of wind electromechanical complex with direct wind power conversion into electric power that provides energy-efficient operation modes of wind power plant electromechanical complex. The economic efficiency of using wind power plant in underground iron-ore mining was proved.